Provincial electoral districts: according to The Representation act, 1966 (33A) - Lands & Surveys Branch (Producer)
An electoral map of the Province of Ontario as of 1966. Legend on the left side of the map divides cities and towns into population brackets. Geographic boundaries, railways, First Nations reserves, provincial parks, and elevations are noted in the legend. Areas highlighted in red are covered in more detail in inset maps. Scale is 1:506,880. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .